IMPROVING STUDENTS’ SKILLS IN ACADEMIC ARGUMENTATIVE ESSAY THROUGH THE APPLICATION OF GENRE-BASED APPROACH - Asnita Sirait; Kristining Seva; Thomson Radesman Lingga (IKIP Siliwangi, 2023)
This research is motivated by the challenges faced by students in writing academic essay. A method is needed to overcome these problems namely by applying a genre-based approach or genre-based approach (GBA) to writing academic essays especially in general courses (MKU) Bahasa Indonesia. This study uses a class action research method (CAR) with the aim of getting transformation and improve the quality of student achievement results. Analysis of research data carried out with a qualitative descriptive and quantitative approaches. The data in this study in the form of observations, recordings, interviews, documentation taken from the RPP. Source the data of this study are students who took the MKU Indonesian (32 people) and documentation. The data collection technique used is the validation of data obtained from data triangulation results. The results of the research show that the use of the genre-based approach in writing academic essays is significantly increasing the ability to write student argumentative essays. This can be seen from the students' pre-test and post-test scores. The average value of the pretest is 61, 156 and the post-test is 76,375. This shows an increase in the ability to write argumentative text is equal to 15.219 point. The results of this study are expected to be used as a consideration for improving students' writing skills and also producing essay teaching guides in producing academic essays.